Client characteristics and outcomes of the Australian short-term restorative care programme: a cohort study - Lindsey Brett; Angela Collins; Kylie Lemsing; Christopher J. Poulos (BMC Health Services Research)
Abstract Background Restorative care is a goal-oriented, time-limited, multidisciplinary approach to address functional decline in older adults. Within Australia, one form of restorative care available to community-dwelling older adults is the Short-Term Restorative Care (STRC) Programme. Australian government expenditure on such services is high, yet research on programme outcomes is scarce. The primary aim of this study was to provide a descriptive analysis of STRC participant and outcome data from clients’ first STRC episode with a large, aged care provider in New South Wales (NSW), Australia. Secondary aims were: (i) examine any associations between client demographic and outcome measures routinely collected, and (ii) consider the suitability for broader sector use of the clinical and outcome measures routinely collected by the provider. Methods A retrospective, cohort study of STRC client data routinely collected between 1 March 2021 and 28 February 2023 from a large, not-for-profit aged care provider in NSW, Australia. Client demographic data and routinely used clinical and outcome measures (modified Barthel Index, Mini Nutritional Assessment short form, Clinical Frailty Scale, Patient-Reported Outcomes Measurement Information System 10-Question short form - global health, and Goal Attainment Scale light) were collected. Descriptive and inferential analyses were completed to explore available data. Results Four hundred and eighty-four STRC clients were included in this study. The mean age of clients was 81.5 (7.6) and majority were female (56%), born in Australia (49%), had a normal nutritional status on entry (54%), and classified as either pre-frail or mildly frail on entry (66%). The modified Barthel Index, Patient-Reported Outcomes Measurement Information System 10-Question short form - global health, and Goal Attainment Scale light all showed statistically significant improvements. Almost all clients remaining in their own home after exit of the STRC Programme (99%). Conclusions This study looked at detailed data from the STRC Programme in Australia with a large sample over multiple years from a single aged care provider, and the findings suggest it is an effective program for older adults. The data provide insights into different clinical and outcome measures used, identify those that work well with this population, and those that need further consideration.